Prevalence of Vitamin D Deficiency in Pregnant Ladies - Saqib, Shazia; Umer, Sabeena; Bano, Nosheen; Anwar, Zubda; Liaqat, Jawairiah; Khanam, Saadia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the prevalence of vitamin D deficiency (VDD) in pregnant ladies. Study Design: A cross-sectional study. Place and Duration of the Study: Department of Obstetrics & Gynecology, Sialkot Medical College, Sialkot Pakistan from 1st July 2021 to 30th December 2021. Methodology: We included a total of 165 pregnant women aged 18 to 40 years having singleton pregnancy with gestational age below 16 weeks. Three cc blood samples were taken during routine antenatal investigation from all pregnant ladies. The serum vitamin D was asked from the institutional laboratory. Prevalence of VDD, insufficiency and sufficiency were calculated. Results: In a total of 165 pregnant ladies, mean age was noted to be 30.2+5.5 years. There were 90 (54.5%) women who were living in rural areas. Sunlight exposure was less than 1 hour in 104 (63.0%) pregnant ladies. Ninety four (57.0%) women belonged to low socio-economic status. Evaluation of Vitamin D status revealed that 87 (52.7%) women had VDD, 52 (31.5%) vitamin D insufficiency while 26 (15.8%) had normal vitamin D levels. Sunlight exposure < 1 hour (p=0.0001) and low socio-economic status (p=0.0001) were noted to have significantly association with VDD. Conclusion: Among pregnancy ladies, prevalence of VDD was very high. Poor sunlight exposure and low socio-economic status were revealed to have significant association with VDD.